Crisis Communication: Keys to Successfully Overcome 100 First Days of Government - Jordán, Rodrigo (2023)
After a period of governmental pax, at the beginning of an administration, governments continually face communication and governance crises, which destabilize the image achieved in the campaign, with which the next challenge is to build an image of government. After those hundred days of government, administrations must take into account that public opinion has moved to digital spaces, where public matters are discussed and deliberated. So, communication teams must be prepared for digital onslaughts and daily crises. Here is a small manual on how to deal with these situations and how to prepare communication teams to decide which battles are important.